Mechanical Behaviour of the Porous and Foam Aluminium in Conditions of Compression: Determination of Key Mechanical Characteristics - Byakova, O.V.; Vlasov, A.O.; Semenov, M.V.; Zatsarna, O.V.; Gnyloskurenko, S.V. (Металлофизика и новейшие технологии, 2017)
The paper emphasizes harmonized recommendations for mechanical tests of highly-porous aluminium and aluminium foam to be applicable for analysing their compression response under quasi-static loading as well as determining reliable and reproducible results essentially required for practice problems of engineering design. В работе приведены современные рекомендации для механических испытаний высокопористого и вспененного алюминия, которые пригодны для анализа механического поведения этих материалов в условиях сжатия и получения надёжных и воспроизводимых результатов, необходимых для решения задач инженерной практики. В роботі висвітлено новітні унормовані рекомендації стосовно механічних випробувань високопоруватого та спіненого алюмінію, які є придатними для аналізу механічної поведінки цих матеріялів в умовах стиснення та отримання надійних та відтворюваних результатів, істотно необхідних для вирішення задач інженерної практики.